Acidic soil-tolerant tree species identification - M. T. Asmare (Овощи России, 2024)
Previously, surface soil acidity was amended by the application of lime, gypsum, and acidic soil-tolerant crop species. However, their effectiveness in subsurface soil acidity reduction is limited.   Thus, this review paper aimed to screen the tree species that easily overcome such problems.   Scopus, Science Direct, Google Scholar, African journals online, and Google search engine databases were used. A total of 60 acidic soil-tolerant tree species were identified. Acacia auriculiformis, Acacia crassicarpa, Arbutus unedo L., Casuarina junghuhniana, and Erythrina abyssinica were among the extremely acidic soil-tolerant tree species. Whereas Acacia cincinnata, Acacia mangium, Pinus patula, Albizia saman, Citrus x paradisi, and Cassia reticulata were belongs to some of the strong acidic soil tolerant tree species. Generally, the species' acidic tolerance capacity and planting site compatibility should be considered for the success of amendment works. Scaling out these species and large-scale plantations should be done in addition to estimating their relative percent of acidic soil amendment roles. Producing stable food in line with reclaiming acidic soil is achieved through the integration of stress tolerant fruit trees. Research on large-scale plantations, domestication, skilling up and comparative evaluation of their levels of acidic soil amendment capacity should be performed in the future.